2017
DOI: 10.1038/cddis.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

NGS-based transcriptome profiling reveals biomarkers for companion diagnostics of the TGF-β receptor blocker galunisertib in HCC

Abstract: Transforming growth factor-beta (TGF-β) signaling has gained extensive interest in hepatocellular carcinoma (HCC). The small molecule kinase inhibitor galunisertib, targeting the TGF-β receptor I (TGF-βRI), blocks HCC progression in preclinical models and shows promising effects in ongoing clinical trials. As the drug is not similarly effective in all patients, this study was aimed at identifying new companion diagnostics biomarkers for patient stratification. Next-generation sequencing-based massive analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…The results indicated that mRNA levels of two genes, SKIL and PMEPA1, were positively correlated with TGF-β1 mRNA concentrations in HCC tissues and strongly downregulated by galunisertib. 162 The data presented in the study suggest that SKIL and PMEPA1 mRNA levels, used in combination with TGF-β1 mRNA, could be important biomarkers for selecting patients more likely to respond to treatment with galunisertib, providing a pathway toward personalized medicine thanks to a better patients stratification. 162 Ki26894 and SB-435 are other TβRI inhibitors demonstrating positive effects in in vitro experiments using gastric cell lines 163 and CRC, 164 respectively, but these have not yet been tested in clinical trials.…”
Section: Intracellular Level: Signal Transduction Blockade By Recep-mentioning
confidence: 86%
See 1 more Smart Citation
“…The results indicated that mRNA levels of two genes, SKIL and PMEPA1, were positively correlated with TGF-β1 mRNA concentrations in HCC tissues and strongly downregulated by galunisertib. 162 The data presented in the study suggest that SKIL and PMEPA1 mRNA levels, used in combination with TGF-β1 mRNA, could be important biomarkers for selecting patients more likely to respond to treatment with galunisertib, providing a pathway toward personalized medicine thanks to a better patients stratification. 162 Ki26894 and SB-435 are other TβRI inhibitors demonstrating positive effects in in vitro experiments using gastric cell lines 163 and CRC, 164 respectively, but these have not yet been tested in clinical trials.…”
Section: Intracellular Level: Signal Transduction Blockade By Recep-mentioning
confidence: 86%
“…162 The data presented in the study suggest that SKIL and PMEPA1 mRNA levels, used in combination with TGF-β1 mRNA, could be important biomarkers for selecting patients more likely to respond to treatment with galunisertib, providing a pathway toward personalized medicine thanks to a better patients stratification. 162 Ki26894 and SB-435 are other TβRI inhibitors demonstrating positive effects in in vitro experiments using gastric cell lines 163 and CRC, 164 respectively, but these have not yet been tested in clinical trials. More recently, a first human dose study of a new TβRI kinase inhibitor, Vactosertib (TEW-7197, MedPacto), was started as monotherapy in subjects with advanced-stage solid tumors.…”
Section: Intracellular Level: Signal Transduction Blockade By Recep-mentioning
confidence: 86%
“…36 As a TGF-β-inducible gene, PMEPA1 regulated multiple biological process in several types of cancer. 16,20,37 Some reports showed PMEPA1 accelerates the metastasis and EMT through TGF-β signalling. 35 Nevertheless, we demonstrated PMEPA1 promoted migration and invasion, and induced EMT in CRC by activating the BMP signalling pathway with phosphorylation of Smad1 and Smad5.…”
Section: Discussionmentioning
confidence: 99%
“…Both RT-PCR and IHC correlated with the findings of the microarray analysis, and we identified CYP3A4 as a novel, potential clinically useful biomarker for the prognosis of HCC. Although many reports have performed comprehensive microarray analyses of the GEP for patients with HCC (10,(17)(18)(19)(20)(21)(22)(23)(24), the frequency of down-regulation and the prognostic impact of the CYP3A4 gene have not yet described in any reports of integrated microarray analyses. Most of these reports have instead focused on genes related to cancer pathways, and few have focused on the frequency of aberrant gene expression and their impact on the prognosis.…”
Section: Discussionmentioning
confidence: 99%